AUTONOMOUS AUTOMATED ACCUMULATING COMPLEX FOR THE ROBOTIZED PUNCHING PROCESS - Korobko, B. O.; Storozhenko, D. O.; Dryuchko, O. G.; Bunjakìna, N. V.; Khanyukov, V. O. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The accumulating complex was designed for automated loading with discoid billets of unified single-crank presses in robotized punching processes. Advanced variants of the task practical implementation by means of technical, diagram, design upgrading and processing equipment retooling are suggested. Raising the productivity and reliability of the facility, simplifying and cheapening its construction is based on the use and integral combination of possibilities provided by «active», «passive», information parameters influence on the formation and correction of operational production flows of its function supporting systems.